Прогноз споживання нафтопродуктів в Україні за основними видами економічної діяльності - Маляренко , Олена (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
The article presents a mathematical model of demand forecasting for petroleum products with a comprehensive method with the allocation of features of collection and preparation of initial data to forecast their consumption. The mathematical model allows you to predict the consumption of petroleum products in the country (Top-level) and types of economic activity (Down-level) for transport transportation and for transformation into electricity and heat. The purpose of the study is to calculate the prognosis of petroleum products for further compilation of the balance of petroleum products, clarification of methodological approaches to the formation of initial data and the predictive evaluation of the need for petroleum products in the energy sector, provided The expediency of forecasting the total consumption of petroleum products in the country and the enlarged economic activity is noted, since the structure of oil consumption changes significantly depending on the prices for its types and available vehicles. The normative method was used to forecast petroleum products at TOP and Down levels. The forecasts obtained at two levels at significant differences in the results were usually agreed by the vector method of Kulik. Since the form of statistical reporting by type of economic activity for 2020 is not provided by the State Statistics Committee, the initial data on the sectors of the economy were formed from the energy balance By 2040 at the levels of the country and types of economic activity for different structures of the economy: the base 2020 and the forecast. The structural and technological potentials of energy saving in the consumption of petroleum products have been evaluated. It is expected to increase the consumption of petroleum products in the energy sector to restore the country's economy during the post -war period.